Integrated One Health Approaches for Resilient and Sustainable Aquaculture in Bangladesh - Hossain, Sabrina (WorldFish, 2025)
The presentation highlights WorldFish’s integrated One Health initiatives in Bangladesh aimed at strengthening disease prevention, food safety, and AMR mitigation in aquaculture. It outlines collaborations with government and research partners to enhance biosecurity, antimicrobial use surveillance, and capacity-building across five upazilas in Mymensingh. Activities include AMU/AMR monitoring in tilapia farms, agrovet surveys, and antibiotic residue testing in aquaculture environments. Training programs on bacterial isolation, antimicrobial susceptibility testing, and molecular identification have built technical expertise among government and academic institutions. The presentation also addresses challenges such as unregulated antibiotic use, environmental pollution, and climate stress, while promoting solutions like digital tools, rapid diagnostics, biosecurity practices, and ecosystem-based aquaculture models for a more sustainable and resilient blue economy.